Religious coping among muslim parents of children with disabilities: a narrative review - Gumelar Ferdiansyah Pratama; Lia Mawarsari Boediman (Insight: Jurnal Ilmiah Psikologi, 2025)
This narrative review explores how Muslim parents of children with disabilities draw on religious coping (RC) to navigate parenting challenges. The literature search covered three major international databases and manual sources, yielding 136 articles published between 2011 and 2025. In the end, 13 articles met the inclusion criteria and were included in the analysis. The quality and narrative suitability of the articles were evaluated using the SANRA (Scale for the Assessment of Narrative Review Articles) protocol. The review identified three main themes: (1) the types of RC strategies used by Muslim parents, (2) the factors influencing their use of RC, and (3) the impact of RC on well-being and parenting practices. Overall, RC plays an essential role in helping Muslim parents adapt, manage stress, cultivate inner peace, and maintain a sense of meaning and hope in their parenting journey. It also supports the development of positive attitudes, strengthens moral responsibility, and enhances overall well-being. This review underscores the importance of integrating religious perspectives into psychosocial support for families of children with disabilities in Muslim communities.